Elevated Bile Acid 3β,5α,6β-Trihydroxycholanoyl Glycine in a Subset of Adult Ataxias Including Niemann-Pick Type C - Nazgol Motamed-Gorji; Youssef Khalil; Cristina Gonzalez-Robles; Shamsher Khan; Philippa Mills; Hector Garcia-Moreno; Heather Ging; Ambreen Tariq; Peter T. Clayton; Paola Giunti (MDPI AG, 2024)
Ataxia is a common neurological feature of Niemann-Pick disease type C (NPC). In this disease, unesterified cholesterol accumulates in lysosomes of the central nervous system and hepatic cells. Oxidation by reactive oxygen species produces oxysterols that can be metabolised to specific bile acids. These bile acids have been suggested as useful biomarkers to detect NPC. Concentrations of 3β,5α,6β-trihydroxycholanyl glycine (3β,5α,6β-triOH-Gly) and 3β,7β-dihydroxy-5-cholenyl glycine (3β,7β-diOH-Δ5-Gly) were measured in plasma of 184 adults with idiopathic ataxia. All patients were tested with whole genome sequencing containing hereditary ataxia panels, which include NPC1 and NPC2 mutations and other genetic causes of ataxia. Plasma 3β,5α,6β-triOH-Gly above normal (>90 nM) was found in 8 out of 184 patients. One patient was homozygous for the p.(Val1165Met) mutation in the NPC1 gene. The remaining seven included one patient with Friedreich's ataxia and three patients with autoimmune diseases. Oxidative stress is known to be increased in Friedreich's ataxia and in autoimmune diseases. Therefore, this subset of patients possibly shares a common mechanism that determines the increase of this bile acid. In a large cohort of adults with ataxia, plasma 3β,5α,6β-triOH-Gly was able to detect the one patient in the cohort with NPC1 disease, but also detected oxidation of cholesterol by ROS in other disorders. Plasma 3β,7β-diOH-Δ5-Gly is not a potential biomarker for NPC1.